Ukrainian diplomatic mission in Germany in 1918-1923 - Volodymyr Zabolotniuk (Cхід, 2018)
The article considers with the formation and activities in Germany of Ukrainian embassies and consular offices in 1918-1923. Diplomatic institutions were represented in Berlin: the Ukrainian People's Republic of the Central Rada (Ambassador Alexander Sevryuk), the Ukrainian State (baron Fedor Shteyngel), the Ukrainian People's Republic Directory of the UNR (Mykola Porch, Roman Smal-Stotsky). His embassy was formed in Berlin and the Western Ukrainian National Republic (Yevhen Levytsky, Yaroslav Byberovych). But in view of the possible negative reaction of the Entente countries, the ZUNR (WUNR) embassy did not develop widly. Ukraine had its consular offices in Berlin and Munich. The article also mentions the activities of the Ukrainian consular establishment in Danzing (Gdansk), which was closely linked with Germany. The Ukrainian diplomatic structures in Germany were officially recognized by the German authorities and focused their efforts on seeking external support from Ukraine in the struggle against the enemies of its independence.